ANALISIS KETERAMPILAN KERJA MAHASISWA JURUSAN PENDIDIKAN KESEJAHTERAAN KELUARGA TERHADAP KESIAPAN KERJA PADA INDUSTRI FESYEN - Aisyah Fitri R; Anas Arfandi; Syamsidah (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
This study aims to describe the quality of work skills of students majoring in PKK FT UNM and to determine the effect of communication skills, creative thinking skills, critical thinking skills, applied academic skills, and technology use skills on job readiness partially and simultaneously. This type of research is quantitative research. The data was obtained from the value of the Industrial Practice course, the distribution of the questionnaire using the Guttman scale via google form, equipped with unstructured interviews. The population of this research is the 2016 undergraduate students majoring in PKK FT UNM Fashion Design study program who have implemented industrial practices in the 2019/2020 academic year as many as 50 people with a sample of 49 people. The research data were analyzed using simple regression analysis, multiple regression analysis, effective contribution analysis and relative contribution analysis. The results showed that the quality of student work skills was classified as very good based on the value of industrial practice, the value of industrial practice reports, and the value of industrial practice seminars. The R2 value in the simple regression analysis shows that communication skills have the most positive effect, namely 19%, creative thinking skills have a positive effect of 17.1%, applied academic skills have a positive effect of 14.5%, technology use skills have a positive effect of 10.9%, and critical thinking skills with the lowest positive effect of 10.6%. These five variables have a positive effect on job readiness in the fashion industry by 44.6%.